2002
DOI: 10.2337/diabetes.51.6.1708
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Fenofibrate or Simvastatin Treatment of Rats on Hepatic Microsomal Overt and Latent Diacylglycerol Acyltransferase Activities

Abstract: Hepatic triacylglycerol secretion is elevated in insulinresistant states. Microsomal diacylglycerol acyltransferase (DGAT) catalyzes the final reaction in the synthesis of triacylglycerol (TAG). We have previously described two DGAT activities in rat liver microsomes, one overt (cytosol-facing) and one latent (endoplasmic reticulum lumen-facing) (Owen MR, Corstorphine CG, Zammit VA: Overt and latent activities of diacylglycerol acytransferase in rat liver microsomes: possible roles in verylow-density lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 49 publications
2
43
2
1
Order By: Relevance
“…The subsequent use of a second membrane-permeabilizing agent, namely alamethacin, a poreforming peptide that acts through an entirely different membrane permeabilization mechanism, allowed the discrete quantification of overt and latent DGAT activities in situ in cells without disruption of the native ER structure. Importantly, the similarity of the ratios of latent to overt DGAT activities as quantified in whole (rat-derived) McA-RH7777 cells and in rat isolated liver microsomes suggests that our original observations (9,11,12,26) are unlikely to have been due to artifacts arising during the preparation of liver microsomal fractions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The subsequent use of a second membrane-permeabilizing agent, namely alamethacin, a poreforming peptide that acts through an entirely different membrane permeabilization mechanism, allowed the discrete quantification of overt and latent DGAT activities in situ in cells without disruption of the native ER structure. Importantly, the similarity of the ratios of latent to overt DGAT activities as quantified in whole (rat-derived) McA-RH7777 cells and in rat isolated liver microsomes suggests that our original observations (9,11,12,26) are unlikely to have been due to artifacts arising during the preparation of liver microsomal fractions.…”
Section: Discussionmentioning
confidence: 67%
“…We also described how the relative expression of the two activities varies with physiological (11) and nutritional state 4 and responds to treatment of rats with different types of hypolipidemic agent (12). This pathway may also account for the remodeling of TAG that occurs par-ticularly in the sn-3 position before it is secreted (9).…”
mentioning
confidence: 99%
“…Quantitative RT-PCR analysis of the mRNAs from the liver of KK-A y mice indicated that the expression of ACO and MCAD, which are known to be regulated by PPARa and to be involved in b-oxidation in liver, 20 was increased by IHE supplementation. In contrast, the expression of the DGAT2 gene, which plays a vital role in the production of triacylglycerol, 21,22 was reduced by IHE.…”
Section: Discussionmentioning
confidence: 87%
“…DGAT, a ratelimited enzyme of TG synthesis, is a microsomal enzyme expressed abundantly in liver and adipose tissue. It catalyzes the final step in TG synthesis by converting diacylglycerol and fatty acyl-coenzyme A into TG (Yen et al 2008), and its expression is close to PPARa (Waterman & Zammit 2002). In the present study, our results showed that after administration of osthole 5-10 mg/kg for 4 weeks, the hepatic SREBP-1c, DGAT, and FAS mRNA expression were reduced, especially in the osthole 10 mg/kg group (p50.01, Figure 2), suggesting that reduced effects of osthole on FFA and TG were partly related to downregulation of these lipogenic gene expressions via activation of PPARa/g.…”
Section: Resultsmentioning
confidence: 99%